Atividades de peroxidase e polifenoloxidase durante o armazenamento pós - Colheita de yacon (polymnia sonchifolia poep & endl) - Quijano, F. G. [UNESP]; Vilhena, S. M C [UNESP]; Câmara, F. L A [UNESP]; Lima, G. P P [UNESP] (My University, 2002)
The purpose of this study was to investigate the peroxidase and polyphenoloxidase activities during the refrigeration at 4oC of yacon tuberous roots with and without polyethylene packing and compared with untreated roots at regular conditions. It was concluded that refrigeration treatment maintains a low activity of these enzymes and keeps good appearance of the roots.
Peroxidase and polyphenoloxidase activities during yacon postharvest storage
Keywords: Browning; Enzymes; Oxidation; Polymnia sonchifolia; Roots